Carcinogenesis Inhibition of Phenolic Derivatives in Duhat (Syzygium cumini); An in Silico Analysis - Beñanil, Keven; Abayon, Reign Bernadette; Albes, Neil Bryan; Bagtasos, Aaliyah Jesiree; Bautista, Emee Andrea; Bonrostro, Mikaela Joyce; Bulalacao, Andrea Jullien; Cano, Earl Adriane (Asian Pacific Journal of Cancer Biology, 2025)
Background: Colorectal cancer (CRC) is one of the most prevalent types of cancer that is commonly treated with traditional chemotherapy; this approach, however, can be toxic, nonspecific, and occasionally ineffective thus necessitating alternative therapeutic strategies. Epidemiological studies suggest that phytochemicals, particularly phenolic compounds, possess antioxidant and antitumor properties, potentially reducing cancer risk. Given that Syzygium cumini is abundant in tropical and subtropical regions and is rich in phenolic compounds, this study explores its therapeutic potential against CRC, addressing the limitations in conventional cancer treatment methods. Materials and Methods: Molecular docking, dynamics simulation techniques, and ADMET analysis were employed to analyze the binding potential between phenolic compounds from Syzygium cumini to key proteins involved in colorectal cancer pathways, and evaluate the potential drug-likeness and systemic bioavailability of the representative phenolic compounds. Results: The findings revealed that Myricetin-3-Ogalactoside (-10.1), rutin (-8.8), and gallocatechin (-10.0) showed high binding affinities for essential oncogenic and tumor-suppressor proteins, such as MLH1, p53, and BRAF, with rutin showing the highest affinity across proteins targets belonging in different pathways suggesting that this compound could reduce tumor growth, suppress metastasis, and promote apoptosis. These phenolic compounds not only bind effectively to their CRC-related proteins but also have enhanced structural integrity upon ligand binding, increasing its potential as therapeutic agents against colorectal carcinogenesis. Conclusion: The study suggests that further formulation of S. cumini phenolic compounds may be necessary due to bioavailability challenges identified in their ADMET analysis. Myricetin-3-O-rhamnoside and rutin showed limited intestinal permeability, while ellagic acid and gallocatechin showed higher absorption rates and non-toxic characteristics.